2021
DOI: 10.2147/cmar.s291778
|View full text |Cite|
|
Sign up to set email alerts
|

Long Intergenic Non-Coding RNA LINC00885 Promotes Tumorigenesis of Cervical Cancer by Upregulating MACC1 Expression Through Serving as a Competitive Endogenous RNA for microRNA-432-5p

Abstract: Purpose Long intergenic non-protein coding RNA 885 (LINC00885) has been well studied in breast cancer; however, its contribution in cervical cancer remains unclear. In this study, we aimed to determine the detailed functions of LINC00885 in cervical cancer and elucidate the underlying molecular regulation mechanism. Methods The expression status of LINC00885 in cervical cancer was determined using reverse transcription-quantitative polymerase chain reaction and by searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The role of MINCR has been studied in some types of cancer, where it has been found to inhibit the activity of some miRNAs through the ceRNA function [ 24 , 28 , 29 , 30 ]. For example, in bladder cancer cells, MINCR regulates the expression of EZH2 through miR-26a-5p, while silencing MINCR decreases cell proliferation and invasion and increases apoptosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of MINCR has been studied in some types of cancer, where it has been found to inhibit the activity of some miRNAs through the ceRNA function [ 24 , 28 , 29 , 30 ]. For example, in bladder cancer cells, MINCR regulates the expression of EZH2 through miR-26a-5p, while silencing MINCR decreases cell proliferation and invasion and increases apoptosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, bioinformatics analysis and experimental results showed that LINC00885 positively regulated BAZ2A expression and miR-3150b-3p negatively regulated BAZ2A expression, indicating that BAZ2A was regulated by LINC00885/miR-3150b-3p axis. Based on a recent study, LINC00885 could facilitate CC tumorigenesis by sponging miR-432-5p to up-regulate MACC1 [ 34 ]. Results of current rescue assays indicated that LINC00885 regulated CC cell proliferation and apoptosis through miR-3150b-3p/BAZ2A axis.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of this lncRNA is closely associated with a lower survival rate and poor prognosis in breast and cervical cancer patients. 127 , 128 Lu et al 129 demonstrated that high expression of PAX8‐AS1 is associated with poor relapse‐free survival in thyroid cancer patients. However, a recent study reported the tumour suppressor role of PAX8‐AS1.…”
Section: Discussionmentioning
confidence: 99%
“…Abba et al reported the molecular effects of LINC00885 as a new oncogenic lncRNA associated with early breast cancer progression. Overexpression of this lncRNA is closely associated with a lower survival rate and poor prognosis in breast and cervical cancer patients 127,128 . Lu et al 129 demonstrated that high expression of PAX8‐AS1 is associated with poor relapse‐free survival in thyroid cancer patients.…”
Section: Discussionmentioning
confidence: 99%